THE EFFECT OF DIVIDEND POLICY AND COMPANY SIZE ON LEVERAGE (RETAIL COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2016-2020 PERIOD) - Dewi, Aminar Sutra; Tiana, Elma (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
ABSTRACTThis study aims to examine the effect of dividend policy and firm size on leverage. In companies listed on the Indonesia Stock Exchange. The research population is all financial reports listed on the IDX for the 2016-2020 period. The sample was selected using the the purposive sampling method with sample criteria being companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Companies that have complaate financial statements for the 2016-2020 period and obtained a sample of 6 companies. The data source is the company’s annual financial statementstaken through the official website of the Indonesia Stock Exchange (www.idx.co.id) testing using panel data regression analysis with the SPSS program. Dividend policy is measured by the dividend payout ratio (DPR), while company size is measured by (SIZE). The results showed that the dividend policy variable hed a negative and insingnificant effect on leverage, while firm size had a negative and insingnificant effect on leverage.Keywords: Leverage; Dividend Policy; Company Size.